The lmpact of lraqi Administration on the Administrative and Urban Situatuation of Basra City - Sanaa Kareem Rahma / Jaafar Abdul Daim Al- Mansoor ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This research focuses on studying the most important organizations established by the Iraqi monarchy government in 1920 and their impact on various regions in Iraq, including Basra as an integral part of the local  administration. Under these new administrative regulations, Basra became a separate administrative unit managed directly by the governorate's administration, which played a significant role in the urban and civic development of Basra city through its efforts to accomplish numerous urban and service projects that benefitted the people of Basra in general.